If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4=1(x-3)+2x-1
We move all terms to the left:
3x-4-(1(x-3)+2x-1)=0
We calculate terms in parentheses: -(1(x-3)+2x-1), so:
1(x-3)+2x-1
We add all the numbers together, and all the variables
2x+1(x-3)-1
Back to the equation:
-(2x+1(x-3)-1)
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
We calculate terms in parentheses: -(2x+1(x-3)-1), so:
2x+1(x-3)-1
See similar equations:
| 2z÷3=11 | | 14x−3=5x+15 | | 3x+5+3x+18+10x−9=180 | | 4x+3=115 | | 4x+2x+10=46 | | -8n=-6n+10 | | g/10=8 | | 7n-(3n+1)=-5+9 | | 7x-4x+2x+x=24 | | 5/8x+4=3/8x+1 | | 1+x/x+11=0 | | 2/3=t/27 | | 40-2a=8 | | 4x-3=12x-5 | | 6x+1+3x+6+2x+8=180 | | r/72=3/9 | | -17q+5q=12 | | 20-j=4j | | 2(l+3)=3(2l+1) | | -124=4(1+18k) | | –6k+1=–17 | | –6k+1=–17* | | r/18=3/27 | | (X-3)-5(x+7)=10(x+3)-1(7x+5) | | 12y-14=5y=7 | | 3q-4q=12 | | 3x-4=4x+26 | | 8(x+2)=4(2x+9) | | -12=v6 | | 110=2x-9(x+8) | | 4x=3x+ | | x10=-5 |
Equations solver categories
- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions
- How to solve complicated linear equation